2020
DOI: 10.1002/slct.202003993
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies for Hydrazinyl Thiazole Derivatives

Abstract: Hydrazinyl thiazole is frequently encountered in natural as well as in synthetic compounds. It is also an important pharmacophore and has some other useful applications. In this review article, we have compiled different green synthetic procedures for the synthesis of hydrazinyl thiazole derivatives. Also, the critical analysis of different synthetic schemes will help to understand the lacks in developed procedures and to develop new methodologies regarding its synthesis, specially using heterogeneous organoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our literature survey revealed that there are a range of approaches for its synthesis. 6 Pioneering research studies have aimed to develop a one-pot MCR strategy that included catalyst-free, 7 catalyst and solvent-free, 8 homogeneous, 9 and heterogeneous catalysis, 10 to achieve a simple synthesis of this class of compounds. Some of the foregoing synthetic methods demand the use of costly transition metal catalysts, which are immensely crucial for the synthesis of 2-hydrazinyl thiazole.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature survey revealed that there are a range of approaches for its synthesis. 6 Pioneering research studies have aimed to develop a one-pot MCR strategy that included catalyst-free, 7 catalyst and solvent-free, 8 homogeneous, 9 and heterogeneous catalysis, 10 to achieve a simple synthesis of this class of compounds. Some of the foregoing synthetic methods demand the use of costly transition metal catalysts, which are immensely crucial for the synthesis of 2-hydrazinyl thiazole.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit the wide range of applications for hydrazinyl thiazoles, their synthetic methods [13,[17][18][19][20] have yet to be fully explored, and more studies are needed. In the recent past, interest has been resurgent in developing green synthetic nano-based catalytic models in the synthesis of biologically important precursors in the fields of organic synthesis and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%